Poly hydroxyalkanoates (PHA): Role in bone scaffolds - Ruby Dwivedi; Rahul Pandey; Sumit Kumar; Divya Mehrotra (Journal of Oral Biology and Craniofacial Research)
Polyhydroxyalkanoates (PHA) are prokaryotic macromolecules accumulated within the cytoplasm as granules. Due to their suitable mechanical properties, biocompatibility, degradation time, ability to be blended, surface modified, and form copolymers, it is widely used in medical devices and as scaffolds in bone tissue engineering. This review describes in brief the production and extraction sources, physico-chemical characteristic, mechanical properties, degradation rate and applications of various PHAs and its copolymers with special emphasis to its role as scaffolds in bone tissue engineering.